PERLINDUNGAN HUKUM HAK ATAS TANAH ADAT DI SALENA KECAMATAN ULUJADI - Maryam Purwaningsi (INSANI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
This Salena Indigenous People regarding the demarcation of the land of the Salena indigenous people, Ulujadi District, Palu City which resulted in BPKH Wilayah XVI Palu being sentenced to customary fines by the Salena Customary Chief and the absence of legality regarding the land of the Salena indigenous people. In this research, there is one problem formulation, namely how is the legal protection of indigenous peoples’ land in Salena, Ulujadi District? The purpose of this research is to find out the legal protection of indigenous peoples’ land in Salena, Ulujadi District. The result of this research shows that the protection of the land of Salena indigenous people until now has not received specific protection as outlined in the Regional Regulation of Palu City. This indicates that the existence of customary rights of the Salena community is still limited to recognition from the government as regulated in the Legislation. However, its implementation in the region has not gone well, this is in line with the absence of a Recognition Letter issued by the Palu City Regional Government or the City Regional Regulation that recognises and protects the land of the Salena indigenous people. So, if there is no protection implemented in the Palu City Region, it is possible that there will be disputes in the future. Abstrak Masyarakat Adat Salena mengenai pematokan tanah masyarakat adat Salena, Kecamatan Ulujadi, Kota Palu yang berujung BPKH Wilayah XVI Palu dijatuhi denda adat oleh Ketua Adat Salena serta belum adanya legalitas mengenai tanah masyarakat adat salena. Pada penelitian ini terdapat satu rumusan masalah yaitu bagaimana perlindungan hukum terhadap tanah masyarakat adat di Salena Kecamatan Ulujadi?. Tujuan penelitian ini adalah untuk mengetahui perlindungan hukum terhadap tanah masyarakat adat di Salena Kecamatan Ulujadi. Hasil penelitian ini menunjukan bahwa Perlindungan atas tanah masyarakat adat Salena sampai saat ini belum mendapatkan perlindungan secara spesifik yang dituangkan dalam Peraturan Daerah Kota Palu. Hal ini bertanda bahwa keberadaan hak ulayat masyarakat salena masih sebatas pengakuan dari pihak pemerintah sebagaimana yang telah diatur dalam Peraturan Perundang- Undangan. Namun untuk implementasinya ke daerah belum berjalan dengan baik, hal ini sejalan dengan belum adanya Surat Pengakuan yang dikeluarkan oleh Pemerintah Daerah Kota Palu atau Peraturan Daerah Kota yang mengakui serta melindungi tanah masyarakat adat salena. Maka, jika dibiarkan terus menerus tidak ada perlindungan yang di implementasikan di Daerah Kota Palu, tidak menutup kemungkinan akan terjadi sengketa kedepannya.